Mesenchymal Stem Cell–derived Extracellular Vesicles: An Emerging Therapeutic Strategy for Diabetic Wound Healing - Meiliana, Anna; Dewi, Nurrani Mustika; Wijaya, Andi (The Prodia Education and Research Institute (PERI), 2024)
One of the most serious side effects of diabetes is diabetic foot ulceration (DFU). It is a severe and extremely morbid illness that has been linked to higher mortality on its own. The development of effective wound therapeutics in the future may be influenced by our current and developing understanding of wound pathophysiology. By reestablishing cellular functioning, small extracellular vesicles (sEVs), a crucial medium for intercellular communications, exhibit encouraging therapeutic potential in the treatment of DFU. Mesenchymal stem cell (MSC) derived exosomes and engineered extracellular vesicles (EVs) have the potential to aid in the healing of wounds. Along with encouraging the growth and stimulation of endothelial cells, keratinocytes, and fibroblasts, they also have immunomodulatory and anti-inflammatory properties. They help prevent damaged cells from dying, revitalize senescent cells, and boost angiogenesis. MSC-EVs can be a safe, effective and ethical therapy for DFU by increasing M2 macrophages polarization, improving the proliferation, reducing scar, and improving angiogenesis.KEYWORDS: mesenchymal stem cell, extracellular vesicle, diabetic wound, wound healing